Using Grounded Theory - Michael Thomas (Grounded Theory Review: An International Journal, 2025)
This is a review of new book by Helen Scott that serves as a helpful primer for both novice and seasoned grounded theory researchers. The review highlights the essential components of the book and summarizes is main contributions.